The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.jnatprod.5b00195
|View full text |Cite
|
Sign up to set email alerts
|

ent-Abietane-Type and Related Seco-/Nor-diterpenoids from the Rare Chloranthaceae Plant Chloranthus sessilifolius and Their Antineuroinflammatory Activities

Abstract: Fourteen new ent-abietane-type diterpenoids, sessilifols A-N (1-14), and three related new norditerpenoids (15-17) were isolated from Chloranthus sessilifolius. The absolute configurations were determined by single-crystal X-ray diffraction analysis, the modified Mosher's method, and/or the observed Cotton effects in their electronic circular dichroism spectra. Sessilifols A (1) and B (2) possess an uncommon five-membered C-ring rearranged by oxidative cleavage of the C-13/C-14 bond in abieta-7,13-diene follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…Monoterpenes, such as (−)-myrtenol, have shown an in vitro antioxidant activity, which prevents lipid peroxidation, as well as removing nitrite ion concentrations and hydroxyl radicals [79]. In addition, new (ent-)abietane-type diterpenoids and norditerpenoids were isolated from Chloranthus sessilifolius plants [80]. These authors showed that the former compound inhibited NO production in LPS-stimulated BV-2 microglial cells, which evinces the antineuroinflammatory and antioxidant activities of these diterpenoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoterpenes, such as (−)-myrtenol, have shown an in vitro antioxidant activity, which prevents lipid peroxidation, as well as removing nitrite ion concentrations and hydroxyl radicals [79]. In addition, new (ent-)abietane-type diterpenoids and norditerpenoids were isolated from Chloranthus sessilifolius plants [80]. These authors showed that the former compound inhibited NO production in LPS-stimulated BV-2 microglial cells, which evinces the antineuroinflammatory and antioxidant activities of these diterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…These authors showed that the former compound inhibited NO production in LPS-stimulated BV-2 microglial cells, which evinces the antineuroinflammatory and antioxidant activities of these diterpenoids. Besides, (ent-)abietenes have been suggested as therapeutic alternatives for the treatment of neurodegenerative and other aging-associated diseases [80]. Moreover, the triterpenoid saponin (21-O-angeloyltheasapogenol E3; ATS-E3) isolated from Camellia sinensis plant seeds inhibited phagocytic uptake, ROS generation, and NO production by suppression of protein kinase B (PKB), also known as AKT; I kappa B kinase (IKK); and factor nuclear kappa B (NF- κ B)-dependent inflammatory pathways in macrophage culture [78].…”
Section: Discussionmentioning
confidence: 99%
“…Sessilifol C ( 305 ) was a rare 7,8-seco-9-spiro-fused ent -abietane, while sessilifol O ( 306 ) represented the naturally-occurring 14-norabietane diterpenoid. Sessilifols F ( 307 ) and I ( 308 ) showed anti-neuroinflammatory activities against the NO production in LPS-stimulated murine BV-2 microglial cells with IC 50 values of 8.3 and 7.4 μM ( N -monomethyl-L-arginine ( L -NMMA), 14.4 μM) (Wang et al, 2015h ). Two heterodimers of an isopentenyl indole and a coumarin unit by a new fused cycloheptene linker, exotines A ( 309 ) and B ( 310 ), were obtained Murraya exotica roots.…”
Section: Terrestrial Plantsmentioning
confidence: 99%
“…To the best of our knowledge, only crude polysaccharides, flavonoids, and chlorogenic acid were previously detected by analytic methods from tiny samples of roots, stems, and leaves collected off the cliff of the Zhangjiajie Mountains located in Hunan Province, P. R. China . As part of our ongoing search for novel antineuroinflammatory natural products from plants , the whole plant of O. rupifraga was phytochemically studied, resulting in the isolation of a new lignan ( 1 ), two new oleanane triterpenoids ( 2 , 3 ), and a new cholestane glycoside ( 4 ), along with 13 known compounds ( 5 – 17 ; Fig . ).…”
Section: Introductionmentioning
confidence: 99%